The Role Of Country Governance On The Relationship Between Firm Governance And Firm Value In Emerging Markets - Soong, Yu Qing (2019)
Corporate scandals and financial crisis have drawn public attention to acknowledge the importance of corporate governance. Corporate governance is defined as how a firm is being controlled and directed. In order to compete in the competitive environment, firms have to comply and practice corporate governance as they are constantly being monitored by the investors, shareholders, public, regulatory agencies, policy makers and all relevant stakeholders. Recent studies tend to place more emphasis on the developed markets as compared to the emerging markets.